PENINGKATAN MOTIVASI BELAJAR SISWA MELALUI PENERAPAN METODE HYPNOTEACHING PADA MATA PELAJARAN IPS SISWA KELAS V SD NURUL IJTIHAD PUJUT LOMBOK TENGAH - Buana Sari; Baiq Arnika Sa'adati; Muhamad Sadli (Universitas Islam Malang, 2019)
This research aims to improve the learning motivation students through the application of hpnoteaching methods on social studies fifth grade of Nurul Ijtihad Pujut elementary school even semester 2016-2017. The type of this research is classroom action research with Kurt Lewinâ€™s model. This research consisted of two cycles, and each cycle is made up of one meeting, data collection techniques were observation, questionnaires, and documentation. The observation used to see the activities of the teacher and the students while the questionnaires used to see student learning motivation. Data analysis was using techniques analysis quantitative descriptive. The object of this study is the fifth grade of elementary school Nurul Ijtihad Pujut. The results showed that the implementation of hpnoteaching method could improve student learning motivation. It can be seen from achieving category values, in the first cycle, the average score of learning motivation is 28 with a percentage of 40% with quite high category, and 60% high category. In the second cycle, the average score of learning motivation is 41.6 with a percentage of 30% high category and 70% very high category.Â